Unravelling the role of vacancies in lead halide perovskite through electrical switching of photoluminescence - Cheng Li (Nature Portfolio, 2018)
Methylammonium lead triiodide perovskite based solar cells have attracted lots of attention but many physical characteristics of this material remain elusive. Here Li et al. reveal the role of defects in the carrier recombination dynamics in photoluminescence experiments and present a model to describe it.